Relationship marketing practices and customer loyalty: special emphasizes on business to business context - Dayarathna, H.P.N.P (University of Jaffna, 2016)
Relationship marketing is identified as the most important concept under the marketing paradigm and it is also recognized as the strategic concept to the business to business practices to enhance the customer loyalty within the hyper competitive environment. In this context, the study examined the influence of relationship marketing on customer loyalty with six underpinning dimensions of relationship marketing practices as trust, competence, communication, conflict handling, commitment and bonding. The study employs exploratory factor analysis and multiple regression analysis to come to the general conclusion which is based on the sample respondents. Study covered the Colombo district and applies the facts on business customers. Results of the study might stress the underpinning relationship between relationship marketing and customer loyalty. A questionnaire was completed by 108 customers of Arpico Interiors, who represent the executive level. The findings revealed that the RMP significantly influence on CL in Interiors Company. Among the dimensions competence, commitment and bonding enhance the customer loyalty. Implications are derived from the results and recommendations are discussed.
Keywords: Relationship marketing practices and customer loyalty: special emphasizes on business to business context; Customer loyalty; Relationship marketing practices